2013
DOI: 10.1111/ajd.12016
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasculitis and multi-focal neurological deficits due to allopurinol-induced hypersensitivity syndrome

Abstract: Drug-induced hypersensitivity syndrome (DIHS) is a multi-system syndrome resulting from an idiosyncratic reaction to medication. While it commonly results in multi-organ involvement, particularly the liver, there are few reports of DIHS causing cerebral vasculitis and neurological deficits. We report the case of a 63-year old woman with DIHS secondary to allopurinol leading to multiple neurological deficits with magnetic resonance imaging findings consistent with a cerebral vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It is unclear whether allopurinol administered to our patient prior to the first episode of carotidynia had a role in the development of the initial bout of symptoms. However, two cases in the literature describe a systemic hypersensitivity response to allopurinol resulting in cerebral vasculitis [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether allopurinol administered to our patient prior to the first episode of carotidynia had a role in the development of the initial bout of symptoms. However, two cases in the literature describe a systemic hypersensitivity response to allopurinol resulting in cerebral vasculitis [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…A fourth case was reported by Lim [11]. A 63-year-old woman with DRESS syndrome associated to allopurinol.…”
Section: Discussionmentioning
confidence: 95%
“…The management is the immediate cessation of the offending drug. High-dose systemic steroids, typically tapered slowly over 4-12 months, are the mainstay of treatment of the more severe cases [11]. While Tohyama [16] and others have demonstrated an association with HHV-6 reactivation at initial presentation and relapse, treatment with systemic corticosteroids alone is adequate in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports on DRESS syndrome triggering cerebral vasculitis [23,24]. In a recent review by Y. Kano et al, it is suggested that regulatory T cells (Tregs) loss of function may be responsible for the association.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review by Y. Kano et al, it is suggested that regulatory T cells (Tregs) loss of function may be responsible for the association. Systemic corticosteroids administration may prevent the gradual loss of Treg function by repairing Treg activity [23]. Similarly, with plasmapheresis, the balance between Treg and other immunoactive cells is restored perhaps averting the pathology of the disease.…”
Section: Discussionmentioning
confidence: 99%